Predictors of sperm retrieval success in first-time and repeated Micro-TESE for nonobstructive azoospermia - Sulieman Alriyalat; Mohammad Ghassab Deameh; Hamzeh Farraj; Jad Khaled Alsmadi; Baha’ Aldeen Bani Irshid; Hammam Abu Rahmeh; Ahmad Khaled Awawdeh; Mohammad Ahmad Mubarak; Ali Fawzey Ababneh; Wa’el Ahmad Bani Amer; Mohammad Al-Zubi (Future Science OA)
Introduction Microdissection testicular sperm extraction (micro-TESE) is the preferred sperm retrieval method, although success rates vary based on factors such as age and hormone levels. We evaluate sperm retrieval outcomes in first-time and repeated micro-TESE, identifying predictors of success to guide clinical management.Material and methods Retrospective study analyzed 152 men with nonobstructive azoospermia (NOA) who underwent micro-TESE between 2020 and 2022. Patients were grouped based on sperm retrieval outcomes, and clinical, demographic and hormonal factors were assessed. Comparisons were made between first-time and repeat micro-TESE cases.Results Sperm retrieval rate was higher for first-time TESE cases (64.6%) than repeated TESE cases (28.8%, p < 0.01). Repeated TESE cases were older, had higher smoking rates, and exhibited significantly elevated follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, with lower total testosterone (p < 0.01). In repeated TESE cases, no significant differences in age, smoking status or hormone levels were found between successful and failed attempts.Conclusion First-time micro-TESE users had a significantly higher sperm retrieval rate than those undergoing repeated attempts. Repeated TESE was associated with older age, higher smoking rates and adverse hormonal profiles. Larger studies are needed to validate these findings and optimize patient selection for repeated micro-TESE.